Praktik Tradisi Mangupa dan Relevansinya dengan Prinsip-Prinsip Hukum Islam di Desa Mompang Lombang Kecamatan Dolok - Maruba Rambe; Lanna Rambe (KAMPUS AKADEMIK PUBLISING, 2026)
The Mangupa tradition is one of the cultural customs of the Mandailing people that is still preserved today. This tradition is carried out during various important events, such as weddings, thanksgiving ceremonies, the giving of advice, and other traditional ceremonies aimed at offering prayers, motivation, and hopes for safety to an individual. This study aims to examine the practice of the Mangupa tradition in Mompang Lombang Village, Dolok Subdistrict, and to analyze its relevance to the principles of Islamic law. This study employs a qualitative research method with an empirical approach. Data were collected through observation, interviews, and documentation involving traditional leaders, religious figures, and local residents. The results indicate that the Mangupa tradition in Mompang Lombang Village is still practiced in accordance with Mandailing customs passed down through generations. The Mangupa procession embodies social, moral, and spiritual values, such as fostering social bonds, mutual cooperation, respect for others, and the offering of advice aimed at promoting goodness. From an Islamic legal perspective, the practice of the Mangupa tradition is fundamentally consistent with the principles of Islamic sharia as long as it does not contain elements of shirk (polytheism), superstition, or practices contrary to Islamic teachings. This tradition can be categorized as ‘urf (custom) that is acceptable under Islamic law because it serves the public interest and does not contradict the textual sources of Islamic law. Therefore, the Mangupa tradition is strongly aligned with the principles of Islamic law, particularly in terms of maintaining social relationships, instilling values of goodness, and strengthening community solidarity.